(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2025)
This study aims to analyze the level of satisfaction of train passengers using the Servqual method, which includes five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The study population was passengers of the Bias Madiun-Solo train with a sample of 100 respondents selected using bootstrap sampling techniques. Data were collected through a Likert-based questionnaire and analyzed using descriptive methods and gap analysis. The results showed the highest satisfaction score in the Assurance dimension (4.08) and the lowest in Reliability (3.90), indicating the need for improvements in the timeliness and accuracy of information. Recommendations for improvement include improving physical facilities, staff training, and optimizing information systems. This study contributes to PT Kereta Api Indonesia in improving service quality and passenger satisfaction, as well as being a reference for further research related to railway transportation.